2004
DOI: 10.1038/sj.emboj.7600158
|View full text |Cite
|
Sign up to set email alerts
|

Lesion (in)tolerance reveals insights into DNA replication fidelity

Abstract: The initial encounter of an unrepaired DNA lesion is likely to be with a replicative DNA polymerase, and the outcome of this event determines whether an error-prone or errorfree damage avoidance pathway is taken. To understand the atomic details of this critical encounter, we have determined the crystal structures of the pol a family RB69 DNA polymerase with DNA containing the two most prevalent, spontaneously generated premutagenic lesions, an abasic site and 2 0 -deoxy-7,8-dihydro-8-oxoguanosine (8-oxodG). I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
217
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(229 citation statements)
references
References 48 publications
12
217
0
Order By: Relevance
“…Accommodation of lesion-induced template distortions by high-fidelity polymerases has also been observed for other types of DNA lesions that are less bulky than G-AF or G-AAF but also impede DNA replication. Structures of 8ox-oguanine, cyclobutane pyrimidine dimers, or abasic lesions bound by T7 DNA polymerase (67,68), RB69 polymerase (69,70), or BF (62) reveal that template distortions induced by these lesions do not necessarily result in distortions to the polymerase active site. However, interactions between the lesioned duplex and the polymerase are lost, thereby impairing lesion bypass and promoting partitioning of the DNA duplex to the exonuclease domain in the case of RB69 (69,70).…”
Section: Anti Conformation Of G-af Promotes Accurate Replication-mentioning
confidence: 99%
See 1 more Smart Citation
“…Accommodation of lesion-induced template distortions by high-fidelity polymerases has also been observed for other types of DNA lesions that are less bulky than G-AF or G-AAF but also impede DNA replication. Structures of 8ox-oguanine, cyclobutane pyrimidine dimers, or abasic lesions bound by T7 DNA polymerase (67,68), RB69 polymerase (69,70), or BF (62) reveal that template distortions induced by these lesions do not necessarily result in distortions to the polymerase active site. However, interactions between the lesioned duplex and the polymerase are lost, thereby impairing lesion bypass and promoting partitioning of the DNA duplex to the exonuclease domain in the case of RB69 (69,70).…”
Section: Anti Conformation Of G-af Promotes Accurate Replication-mentioning
confidence: 99%
“…Structures of 8ox-oguanine, cyclobutane pyrimidine dimers, or abasic lesions bound by T7 DNA polymerase (67,68), RB69 polymerase (69,70), or BF (62) reveal that template distortions induced by these lesions do not necessarily result in distortions to the polymerase active site. However, interactions between the lesioned duplex and the polymerase are lost, thereby impairing lesion bypass and promoting partitioning of the DNA duplex to the exonuclease domain in the case of RB69 (69,70). Rather than bypass lesions using mechanisms of replication for unmodified DNA, high-fidelity polymerases employ non-templated incorporation of dATP (the "A" rule; Ref.…”
Section: Anti Conformation Of G-af Promotes Accurate Replication-mentioning
confidence: 99%
“…The rear wall of this binding pocket, which includes residues L561, N564 and S565 as shown in Fig. 3 of (12), is presumed to reinforce the coplanar arrangement of the nascent base pair (12). According to the ternary structure of RB69 pol (29), the side chain of L561 is an obvious protrusion into the nucleotide binding pocket that may clash with a bulge on the major groove side of a mispair.…”
mentioning
confidence: 99%
“…S1) have shown that purines, in particular adenosine, and to a lesser extent guanosine, are most frequently incorporated opposite the lesion. The strong preference for adenosine has been termed "A-rule" (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%